A Patient with a Right Atrium Mass and Congenital Heart Disease: A Challenging Diagnosis of a Stubborn Disease - Wenyan Wang; Huaicong Long; Zhiying Zhao (Case Reports in Cardiology)
Cardiac lymphoma is extremely rare. An intracardiac mass has rarely been reported to be the cardiac involvement of extranodal lymphoma. It is difficult to establish a final diagnosis via routine examinations. The ability of an echocardiogram to characterize tissue is limited; systemic (18)F-FDG PET/CT scans provide important information for both staging and response assessment in patients with lymphoma. A 68-year-old Chinese male with a second patent foramen ovale (PFO) and an interventricular septal defect presented at our institute with persistent fever, shortness of breath, repeated paroxysmal supraventricular tachycardia (PSVT) attack, and rapidly progressing superior vena cava syndrome. The patient also presented with a mass located in the upper right atrium and superior vena cava which was detected by echocardiogram. (18)F-FDG PET/CT scan revealed a pathological increase of (18)F-FDG uptake in the atrial mass and several other extracardiac lymph nodes. Lymph node biopsy was positive for large B-cell lymphoma. Immunohistochemistry revealed intense and diffuse expression of CD20, CD10, BCL-6, and Ki-67. The patient died without any chemotherapy 18 days after hospital discharge.